Retinal degeneration in primary-progressive multiple sclerosis: A role for cortical lesions?. (January 2017) - Petracca, Maria; Cordano, Christian; Cellerino, Maria; Button, Julia; Krieger, Stephen; Vancea, Roxana; Ghassemi, Rezwan; Farrell, Colleen; Miller, Aaron; Calabresi, Peter A; Lublin, Fred; Inglese, Matilde
Background: Retinal atrophy in multiple sclerosis (MS) is secondary to optic nerve focal inflammation and to injury of the posterior visual pathway. Objectives: To investigate the contribution of cortical lesions (CLs) to retinal pathology in primary-progressive multiple sclerosis (PPMS). Methods: We performed a cross-sectional evaluation of 25 patients and 20 controls, relating magnetic resonance imaging (MRI) metrics of visual pathway integrity with parameters derived from spectral-domain optical coherence tomography (peripapillary retinal nerve fiber layer (RNFL) thickness, ganglion cell + inner plexiform layer (GCIPL) thickness, and macular volume (MV)). Results: Mean RNFL, GCIPL thickness, and MV were significantly reduced in patients compared to controls. MV and GCIPL thickness were significantly correlated with visual acuity. RNFL thinning was associated with thalamus and visual cortex volume (respectively, p  = 0.01 and p  < 0.05). In addition to thalamic volume, GCIPL thinning was associated with CLs and intracortical lesion number and volume, leucocortical lesion volume (all p  ⩽ 0.05) while MV decrease was associated with CLs volume ( p  = 0.05) and intracortical lesion number and volume ( p  < 0.05). Conclusion: Our results suggest that RNFL thinning and GCIPL thinning/MV decrease may be explained by alternative mechanisms including retrograde trans-synaptic degeneration and/or a common pathophysiologic process affecting both the brain with CLs and the retina with neuronal loss.